Crescimento, índices fisiológicos e produtividade de cultivares de feijoeiro sob diferentes níveis de adubação - Santos, Letícia Andriani dos [UNESP]; Soratto, Rogério Peres [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Gonsales, Jaqueline Regiani [UNESP] (FapUNIFESP (SciELO), 2015)
Knowledge of the accumulation and distribution of phytomass in common bean plants under different levels of fertilization can improve crop management. The objective of this study was to evaluate growth, physiological indices and yield of common bean cultivars under different levels of NPK fertilization. The experiment was carried out on a dystroferric Red Nitosol , in Botucatu, State of São Paulo, in a split plot randomized block design, with four replications. Plots were constituted of six treatments (Pérola without fertilization, Pérola with 50% of recommended fertilization, Pérola with 100% of recommended fertilization, IAC Alvorada without fertilization, IAC Alvorada with 50% of recommended fertilization, and IAC Alvorada with 100% of the recommended fertilization) and subplots were made up by seven harvest times during the growth cycle. The NPK fertilization increased similarly the dry matter accumulation, yield components, and grains yield of cultivars of Pérola and IAC Alvorada. Under recommended fertilization, IAC Alvorada cultivar showed higher leaf area index and leaf dry matter accumulation than Pérola; however, with no effects on the increase of grain yield. Regardless of treatment, the maximum dry matter accumulation was achieved at 80 DAE and the highest crop growth rate occurred at 55 DAE.

Conhecimentos sobre o acúmulo e a distribuição da fitomassa do feijoeiro comum, sob diferentes níveis de adubação, podem auxiliar no manejo da cultura. Este trabalho objetivou avaliar o crescimento, os índices fisiológicos e a produtividade de cultivares de feijão, sob diferentes níveis de adubação NPK. O experimento foi conduzido em um Nitossolo Vermelho distroférrico, no município de Botucatu, SP, no delineamento experimental de blocos casualizados, em parcelas subdivididas, com quatro repetições. As parcelas foram constituídas por seis tratamentos (‘Pérola’, sem adubação; ‘Pérola’, com 50% da adubação recomendada; ‘Pérola’, com 100% da adubação recomendada; ‘IAC Alvorada’, sem adubação; ‘IAC Alvorada’, com 50% da adubação recomendada e ‘IAC Alvorada’, com 100% da adubação recomendada) e, as subparcelas, por sete épocas de coletas no decorrer do ciclo. A adubação NPK aumentou os acúmulos de matéria seca, os componentes da produção e a produtividade de grãos dos cultivares Pérola e IAC Alvorada de forma semelhante. O cultivar IAC Alvorada apresentou maiores índices de área foliar e matéria seca de folhas, quando comparados com os de Pérola, sob adubação NPK recomendada, porém, sem esses índices refletirem-se em maior produtividade de grãos. O máximo acúmulo de matéria seca foi alcançado aos 80 DAE e a maior taxa de crescimento da cultura ocorreu aos 55 DAE, independentemente do tratamento.
Growth, physiological indices and yield of common bean cultivars under different levels of fertilization
Keywords: Dry matter partitioning; Growth analysis; Growth rate; Leaf area index; Phaseolus vulgaris L.; Phaseolus vulgaris L.; Análise de crescimento; Partição de matéria seca; Índice de área foliar; Taxa de crescimento